Relationships between the 1-repetition maximum of the power cleans and acceleration ability from a crouch start in sprinters - Mimura, K.; Yanaoka, T. (Journal of Science and Medicine in Sport, 2024)
Introduction: Acceleration ability is one of the important factors for 100 m sprinting performance. Triple extension of the ankle, knee, and hip was required to quickly raise the sprinting velocity from a crouch start. Although the power clean has been used for triple extension training, the relationship between an acceleration ability and the 1-repetition maximum (1RM) of the power clean has not been investigated. In addition, this relationship may differ between sprinters because of differences in strategies to increase sprinting speed (i.e., high stride frequency group or high stride length group). Therefore, this study aimed to clarify the relationships between the 1RM of the power clean and acceleration ability from a crouch start in sprinters.